The Effect of Knowledge Sharing and Employee Competence on the Performance of Customs and Excise Apparatus. - Mauren Paulina Schelling; Ni Wayan Sumetri; Wayan Gede Suka Parwita (ProBisnis : Jurnal Manajemen, 2026)
Employee performance is a primary determinant of organizational efficacy, particularly in government agencies obligated to deliver exceptional public services. This study investigated the partial and simultaneous effects of knowledge sharing and employee competence on the performance of apparatus at the Ngurah Rai Medium Customs and Excise Supervision and Service Office (KPPBC). Employing a quantitative causal research design, the population comprised 289 employees. A sample of 74 respondents was selected utilizing the Slovin formula and simple random sampling. Primary data were collected via structured Likert-scale questionnaires and analyzed using multiple linear regression in SPSS. The findings demonstrated that knowledge sharing exerted a positive and significant effect on employee performance. Furthermore, employee competence also demonstrated a positive and significant impact, emerging as the most dominant predictor in the model. Simultaneously, both variables significantly enhanced overall employee performance. It is concluded that fostering a collaborative knowledge-sharing culture and systematically upgrading human capital competencies are imperative for optimizing operational outcomes. Management is advised to digitalize knowledge transfer platforms and mandate continuous professional certifications.